Intensity-Modulated Radiation Therapy for Esthesioneuroblastoma: 10-Year Experience of a Single Institute - Bao, Cihang; Hu, Weixu; Hu, Jiyi; Dong, Yuanli; Lu, Jiade J.; Kong, Lin (Frontiers in Oncology, 2020)
Objectives: To evaluate efficacy and safety of intensity-modulated radiotherapy (IMRT) in the management of esthesioneuroblastoma (ENB). Methods and Materials: A retrospectively analysis of 52 ENB patients treated with IMRT between 8/2008 and 8/2018 was performed. Thirteen of the 44 patients (29.5%) with newly diagnosed and 2 of the 8 patients with recurrent disease presented regional lymph node metastasis. The median dose of IMRT was 66 (range 52.5–75) Gy for all patients. Elective nodal irradiation (ENI) was provided to all excluding 6 patients in this cohort. Results: With a median follow-up time of 32.5 (6 121) months, the 3-year overall survival (OS), progression-free survival (PFS), local progression-free survival (LPFS), regional progression-free survival (RPFS), and distant metastasis-free survival (DMFS) rates for the entire cohort were 89.7, 69.5, 89.7, 95.1, and 85.4%, respectively. Multivariate analysis revealed that N-classification (N– vs. N+) at presentation was the only significant prognosticators for PFS. No significant prognosticator was identified for other survival outcome. No severe (i.e., grade 3 or 4) IMRT-induced acute toxicity was observed. Severe late toxicities were infrequent (11.5%), which included dysosmia (3.8%), hearing loss (3.8%), radiation brain injury (1.9%), and temporal lobe necrosis (1.9%). Moreover, late ocular toxicity secondary to IMRT was not observed. Conclusion: IMRT produced acceptable 3-year outcomes in terms of OS (89.7%), LPFS (89.7%), and RPFS (95.1%) rates without substantial late adverse effects. Further investigations for a more effective systemic strategy for distant disease control as well as a precision radiation technique for further improvement in local control are needed.